Phase field modeling of dielectric breakdown of ferroelectric polymers subjected to mechanical and electrical loadings. (15th May 2021) - Mi, Zhang; Zhang, Yong; Hou, Xu; Wang, Jie
Abstract: Ferroelectric polymers have attracted increasing attention due to their distinguished dielectric and piezoelectric properties. Dielectric breakdown is one of the main failure behaviors for ferroelectric polymers. Understanding dielectric breakdown of ferroelectric polymers under mechanical and electrical loadings is crucial to their applications in energy storage and conversion devices with high-energy-density. In the present work, a multi-field coupling phase field model is developed to investigate the dielectric breakdown of ferroelectric polymers under mechanical and electrical loadings. To describe the effect of mechanical stresses on the evolution path and critical electric field of dielectric breakdown, a strain-dependent breakdown energy is proposed in the phase field model. The phase field simulations show that a compressive stress restrains the branching of the breakdown path and increases the critical electric field of breakdown. On the contrary, a tensile stress accelerates the branching of the breakdown path and decreases the critical electric field of breakdown. The results in the present work may stimulate further experimental investigations on the effect of mechanical stresses on the dielectric breakdown of ferroelectric polymers and provide a guidance for improving the breakdown strength of ferroelectric polymers through a mechanical way.